CONSUMERISM AS AMERICAN LIFE STYLE IN P. J. HOGAN'S CONFESSION OF SHOPAHOLIC (2009): A SOCIOLOGICAL APPROACH - ASRIRIANTI , RENI DWI (2011)
The major problem of this study is to reveal how consumerism as American life style are reflected in P.J. Hogan's Confession of Shopaholic. The objective of this study is to analyze the movie based on its structural elements and a sociological approach. In analysis, the writer uses qualitative method. The object of the study is Confession of Shopaholic released in 2009 in the United States. The data sources consist of primary and secondary data sources. The primary data source is Rebecca Bloomwood movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the historical background of American in the early twenty first century. The method of the data collection are watching the movie, taking notes the important data, arranging the data based on category of elements of literature review, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, P.J. Hogan wants to describe that people should stay away from consumerism because this is bring bad habit for their life And people have to try stay away this habit. And the second, this movie contains many facts that reflect American life style and American role.